Do trade flows interact in space? Spatial origin-destination modeling~of gravity - Shali Luo; Seung-Whan Choi (International Trade, Politics and Development (ITPD), 2022)
Purpose This study proposes spatial origin-destination threshold Tobit to address spatial interdependence among bilateral trade flows while accounting for zero trade volumes. Design/methodology/approach This model is designed to capture multiple forms of spatial autocorrelation embedded in "directional" trade flows. The authors apply this improved model to export flows among 32 Asian countries in 1990. Findings The empirical results indicate the presence of all three types of spatial dependence: exporter-based, importer-based and exporter-to-importer-based. After further considering multifaceted spatial correlation in bilateral trade flows, the authors find that the effect of conventional trade variables changes in a noticeable way. Research limitations/implications This finding implies that the standard gravity model may produce biased estimates if it does not take spatial dependence into account. Originality/value This paper attempts to offer an improved model of the standard gravity model by taking spatial dependence into account.
Keywords: 330; Spatial dependence; Tobit; Trade